A Phase 2A Trial of the Novel mGluR5‐Negative Allosteric Modulator Dipraglurant for Levodopa‐Induced Dyskinesia in Parkinson's Disease. Issue 9 (23rd May 2016) - Tison, François; Keywood, Charlotte; Wakefield, Mark; Durif, Franck; Corvol, Jean‐Christophe; Eggert, Karla; Lew, Mark; Isaacson, Stuart; Bezard, Erwan; Poli, Sonia‐Maria; Goetz, Christopher G.; Trenkwalder, Claudia; et al.
ABSTRACT: Background: The metabotropic glutamate receptor 5‐negative allosteric modulator dipraglurant reduces levodopa‐induced dyskinesia in the MPTP‐macaque model. The objective of this study was to assess the safety, tolerability (primary objective), and efficacy (secondary objective) of dipraglurant on levodopa‐induced dyskinesia in Parkinson's disease (PD). Methods: The study was a phase 2A double‐blind, placebo‐controlled, randomized (2:1), 4‐week, parallel‐group, multicenter dose‐escalation (from 50 mg once daily to 100 mg 3 times daily) clinical trial involving 76 PD subjects with moderate to severe levodopa‐induced dyskinesia. Safety and tolerability were assessed based on clinical and biological examination and adverse events recording. Secondary efficacy outcome measures included the modified Abnormal Involuntary Movement Scale, UPDRS, and diaries. Pharmacokinetics were measured at 3 visits following a single dose. Results: Fifty‐two patients were exposed to dipraglurant and 24 to placebo. There were no major safety concerns. Two subjects did not complete the study because of adverse events. Most frequent adverse events included dyskinesia, dizziness, nausea, and fatigue. Dipraglurant significantly reduced peak dose dyskinesia (modified Abnormal Involuntary Movement Scale) on day 1 (50 mg, 20%; P = 0.04) and on day 14 (100 mg, 32%; P =0 .04) and across a 3‐hour postdose period on day 14 ( P = 0.04). There was no evidence of worsening of parkinsonism. Dipraglurant was rapidly absorbed (tmax = 1 hour). The 100‐mg dose led to a mean Cmax of 1844 ng/mL on day 28. Conclusions: Dipraglurant proved to be safe and well tolerated in its first administration to PD patients. Its efficacy in reversing levodopa‐induced dyskinesia warrants further investigations in a larger number of patients. © 2016 International Parkinson and Movement Disorder Society